Investigation of the Use of the Thermo-Biological Method in the Return Sludge Line on the Biokinetics of the Activated Sludge Process and the Amount of Excess Sludge Produced - Naeim Banisaeid; Afshin Takdastan; Mahboobeh Cheraghi; Ali Afrous; Reaz Jalilzadeh Yengejeh (آب و فاضلاب)
The volume of produced sludge and its characteristics depend on the quantitative and qualitative characteristics of wastewater, the treatment process, and the operating conditions. Relatively high production of excess biological sludge is considered one of the main drawbacks of aerobic processes used in biological wastewater treatment. This research was conducted in the existing industrial treatment plant of Pars Shiraz sugar factory with a capacity of 5 cubic meters per day. In this research, the effects of temperature changes in the anoxic tank and return line were investigated to increase the biological removal of sludge, reduce the excess biological sludge; also, the effects of temperature changes on the biokinetics parameters in the activated sludge system were analyzed. The average values of the biomass production coefficient (Y) or growth efficiency in the 100-days study period, after the biological reactor reaches a stable state, varied from 0.75 to 0.54 at the return sludge temperature of 40 °C, decreasing to 0.38 at 50 °C and 0.30 at 60 °C in terms of (gMLSS/gCOD). This research demonstrated that while the biomass production coefficient decreases with the increasing return sludge temperature, it also has a negative impact on the quality of the effluent with respect to both quality and biokinetics parameters. The results indicated that the existing conventional bioreactor, with the return sludge temperature of 40 °C, achieves a significantly higher efficiency in removing pollutants, maintainingconventional range of biokinetics parameters, reducing the amount of sludge production coefficient and excess sludge disposal.